The analysis of the degree of 10-13-year-old children's nutrition, dietary habits and physical activity in the selected rural and urban areas of Silesian Province (Poland) - Paweł Jonczyk; Magdalena Potempa-Jeziorowska; Elżbieta Świętochowska; Marek Kucharzewski (SpringerOpen, 2021)
Abstract Background The nutrition disorders in the children's population, in the form of malnutrition, as well as overweight and obesity constitute a significant clinical problem in the contemporary world. As a result of the improper way of children's nutrition, their physical and mental development becomes dysfunctional, which leads in their adult life to serious health consequences, among others, complications of cardiovascular system, metabolic and endocrinological and disorders, improper development of osteoarticular system and mental diseases and social withdrawal. Results Five hundred eighty-nine parents of children aged 10-13 participated in the survey questionnaire, where 304 respondents were constituted by girls (51.61%); however, the remaining 285 people were represented by boys (48.39%). It turned out that overweight and obesity concern approximately 44% of respondents; however, approximately 22% of children have too low body weight in relation to age and sex. While analysing dietary habits, it was observed that main meals are not consumed by all children; breakfast is consumed by approximately 90% of respondents, packed lunch just by 70% and lunch and supper by 90% of respondents. In the course of subsequent analyses, it turned out that over ¾ of respondents declared that their child drinks mineral water every day, only approximately 44% of them drink milk every day; however, almost 18% of children reach for sweet drinks. Children eat sweet or salty snacks too often (over 55% every day or several times a week), resigning from consuming fruit and vegetables (just half of respondents every day), fish and brown bread (below 30% of children eat these products less than once a week); every fifth child dedicates less than 3 h to physical activity, 39% of respondents do exercise from 3 to 5 h a week, the next 25% from 5 to 10 h. Conclusions It was observed in the analysed population that over half of them struggle with the degree of nutrition disorders in the form of overweight and obesity or malnutrition. We may conclude, based on the obtained results, that children have inappropriate dietary habits, consuming too small quantities of fruit and vegetables, brown bread, fish and drinking improper quantities of water and milk. Repeatedly, they replace these full-value products by consuming sweets and salty snacks and by drinking sweet drinks, they also more and more often reach for processed food in fast food bars. What is worrying, it was also observed that in the analysed population, children dedicate too little of their free time to physical activity and additional physical activities.